Multi-criteria-optimisation and desirability indices - Detlef Steuer (Universität Dortmund, Sonderforschungsbereich 475 - Komplexitätsreduktion in Multivariaten Datenstrukturen, 1999)
The basic ideas of Desirability functions and indices are introduced and compared to other methods of multivariate optimisation. It is shown that gradient based techniques are not in general appropriate to perform the numerical optimisation for Desirability indices. The problems are shown for direct modelling of Desirability indices. An example is given to illustrate the sensitivity of estimated optimum factor settings to modelling errors for individual targets.
Keywords: 519; MCO; MCD; MCDA; Desirability Function; Desirability Index; dimension reduction; numerical optimisation